Chronic Oral Administration of Mineral Oil Compared With Corn Oil: Effects on Gut Permeability and Plasma Inflammatory and Lipid Biomarkers - Pieterman, Elsbet J.; Princen, Hans M. G.; Jarke, Annica; Nilsson, Ralf; Cavallin, Anders; Bergenholm, Linnéa; Henricsson, Marcus; Gopaul, V. Sashi; Agrawal, Rahul; Nissen, Steven E.; Hurt-Camejo, Eva (Frontiers in Pharmacology, 2021)
We investigated the effects of chronic oral administration of mineral oil, versus corn oil as control, on intestinal permeability, inflammatory markers, and plasma lipids in APOE*3-Leiden.CETP mice. Mice received mineral oil or corn oil once daily for 16 weeks (15 mice/group). Intestinal permeability was increased with mineral versus corn oil 30 µL/day, shown by increased mean plasma FITC-dextran concentrations 2 h post-administration (11 weeks: 1.5 versus 1.1 µg/mL, p = 0.02; 15 weeks: 1.7 versus 1.3 µg/mL, p = 0.08). Mean plasma lipopolysaccharide-binding protein levels were raised with mineral versus corn oil 30 µL/day (12 weeks: 5.8 versus 4.4 µg/mL, p = 0.03; 16 weeks: 5.8 versus 4.5 µg/mL, p = 0.09), indicating increased intestinal bacterial endotoxin absorption and potential pro-inflammatory effects. Plasma cholesterol and triglyceride concentrations were decreased with mineral oil, with no between-group differences in liver lipids. Fecal neutral sterol measurements indicated increased fecal cholesterol excretion with mineral oil 30 µL/day (+16%; p = 0.04). Chronic oral administration of mineral oil in APOE*3-Leiden.CETP mice increased intestinal permeability, with potential pro-inflammatory effects, and decreased plasma cholesterol and triglyceride levels. Our findings may raise concerns about the use of mineral oil as a placebo in clinical studies.